Pengembangan Desain Wizer.Me Sebagai E-LKPD pada Mata Pelajaran Matematika Materi Bilangan Bulat Kelas VII SMP - Yunita, Rini; Rosmaria, Rosmaria; Novrianti, Novrianti; Masnur, Alkadri (Indo-MathEdu Intellectuals Journal, 2024)
The development of E-LKPD in Grade VII Mathematics Subject of SMPN 5 Linggo Sari Baganti is motivated by a teacher-oriented learning pattern, as well as limitations in the use of digital teaching materials such as E-LKPD. This research aims to produce valid and practical E-LKPD products so that they can be used in the learning process. The type of research used is Research and Development (R&D). The development model used in this study is a 4D model. The 4D model consists of 4 stages, namely define, design, develop and disseminate. The results of the development of E-LKPD were obtained through validity and practicality tests. The product validity test was validated by three validators consisting of one material validator, namely a teacher of Mathematics Class VII SMPN 5 Sari Baganti and two media validators, namely lecturers from the Department of Curriculum and Educational Technology, Padang State University. The product practicality test was carried out by conducting an E-LKPD trial for grade VIIB students of SMPN 5 Linggo Sari Baganti. The results of the validity test by a material expert and two media experts obtained an average score of 4.86, 4.86, and 4.8 respectively which was categorized as "very valid". The results of the practicality test obtained an average score of 4.6 with the category "very practical". Thus, it can be concluded that the E-LKPD developed is suitable for use as a teaching material in Mathematics Class VII Junior High School.